Granulomatous Invasive Infection Involving the Nasal Sinuses and Brain - Roopam Jariwal MS; Arash Heidari MD; Ahana Sandhu MD; Janushe Patel MD; Kamelia Shoaepour MD; Piruthiviraj Natarajan MD; Everardo Cobos MD (SAGE Publishing, 2018)
Invasive fungal infections are commonly associated with some form of immunosuppression. On the nasal epithelial surface, Aspergillus flavus , under favorable conditions, can aggressively breach multiple cell lines invading the local tissues. We present the case of a 35-year-old woman with granulomatous invasive Aspergillus flavus infection involving the nasal sinuses and the brain. Antifungal agents administered in the previous episodes contained the infection; however, the infected site evolved over time surrounded with calcified tissues in the left maxillary sinus. The current infection involved the other side of the maxillary sinus and extended to the orbital cavity eroding the parts of the skull and retro-orbital structures and was treated with a long course of isavuconazole therapy.